Morph-specific differences in life history traits between the winged and wingless morphs of the aphid, Sitobion avenae (Fabricius) (Hemiptera: Aphididae) - Xu, Xiangli; Liu, Xiaoxia; Zhang, Qingwen; Wu, Junxiang (Entomologica Fennica, 2011)
Life history traits were evaluated in the wing polyphenic aphid, Sitobion avenae (Fabricius), by rearing the winged and wingless morphs under the laboratory conditions. Winged morph with large thoraces exhibited a significantly greater morphological investment in flight apparatus than wingless morph with small thoraces. Compared to the winged morph, the wingless morph produced significantlymore nymphs and exhibited significantly faster nymph development rates. In addition, the age at which reproduction first occurred for the winged morph was significantly delayed, and higher mortality was recorded.The results suggest that the fitness differences associated with wingsmay be related to nymph development, adult fecundity, and mortality. Based on these results, the trends and exceptions of life history traits for the wing polyphenic insects are discussed.